Divergent Asymmetric Synthesis of Panowamycins, TM‐135, and Veramycin F Using C−H Insertion with Donor/Donor Carbenes. (25th April 2022) - Bergstrom, Benjamin D.; Merrill, Amy T.; Fettinger, James C.; Tantillo, Dean J.; Shaw, Jared T.
Abstract: Panowamycins are a group of isochroman‐based natural products first isolated from Streptomyces sp. K07‐0010 in 2012 by Satoshi Ōmura and co‐workers that exhibit modest anti‐trypanosomal activity. Herein we demonstrate the first syntheses of these natural products and their epimers. Stereoselective dirhodium‐catalyzed C−H insertion reactions with a donor/donor carbene construct the substituted isochroman core in the key bond‐forming step. The syntheses are completed without the use of protecting groups and feature a late‐stage Wacker oxidation. Incongruent NMR spectra between natural and synthetic samples revealed the structural misassignment of panowamycin A and veramycin F. Computational NMR studies suggested panowamycin A to be an alternate diastereomer, which was confirmed by synthesizing this isomer. Concurrent with this work, in 2021 Mahmud and co‐workers came to the same conclusion with an updated NMR analysis of panowamycin A. In a divergent, asymmetric sequence, we report the synthesis of panowamycin A, panowamycin B, TM‐135, and veramycin F. Abstract : Total Synthesis Shell Game: The asymmetric first synthesis of panowamycin A, panowamycin B, TM‐135, veramycin F, and two unnatural isomers in a stereoselective fashion, featuring a dirhodium‐catalyzed C−H insertion reaction with donor/donor carbenes in the key step to construct the isochroman core is reported. These syntheses reveal a structural misassignment for panowamycin A and computational NMR studies unveil the correct configuration of the natural isomer, which was also synthesized.